Review of Unified DataLake or OneLake of Microsoft Fabrics- applied in a Data Analysis Platform - Ambika Ganapur; Dr. Sumati Ramakrishna Gowda (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Microsoft Fabric is an end-to-end data analytical platform designed for achieve a Unified solutions in a Business Intelligence and Enterprises. It incorporates data movements, processing, ingestion, transformation, real-time event routing, and report building. It provide services like Data Engineering, Data Factory, Data Science, Real-Time Analytics, Data Warehouse, and Databases. This paper examines Microsoft Fabric and its features especially about a One Lake. Microsoft Fabric applied in a real-time analytics, data storage, advanced machine learning capabilities, and robust security protocols. Collection of files, folders and tables which represent the database is a data house . A Data lake is a cloud-based big data analytics service. Which allows storing, processing, and analyzing large amounts of structured and unstructured data. It integrates with other Azure services to provide a full data analysis solution[1].